2017
DOI: 10.2174/1570161115666161104095522
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis and Acute Brain Ischemia in Ischemic Stroke

Abstract: Apoptosis may contribute to a significant proportion of neuron death following acute brain ischemia (ABI), but the underlying mechanisms are still not fully understood. Brain ischemia may lead to stroke, which is one of the main causes of long-term morbidity and mortality in both developed and developing countries. Therefore, stroke prevention and treatment is clinically important. There are two important separate areas of the brain during ABI: the ischemic core and the ischemic penumbra. The ischemic core of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
218
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 363 publications
(236 citation statements)
references
References 0 publications
2
218
0
4
Order By: Relevance
“…Mechanistic studies had revealed that the apoptosis of neuron in hippocampus, corpus striatum and cortex was the causal events leading to sensorimotor dysfunction after HI [33, 34]. In this study, we had performed cylinder rearing test at 14, 21, 28 and 35 days after HI.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistic studies had revealed that the apoptosis of neuron in hippocampus, corpus striatum and cortex was the causal events leading to sensorimotor dysfunction after HI [33, 34]. In this study, we had performed cylinder rearing test at 14, 21, 28 and 35 days after HI.…”
Section: Discussionmentioning
confidence: 99%
“…After the onset of ischemia, the brain cells suffer depletion of energy supply, excessive accumulation of intracellular calcium, overproduction of free radicals, and potentiation of inflammatory responses (Li et al 2015a;Hoque et al 2016). These events initiate a complex sequence of signaling cascades that eventually result in neuronal dysfunction and cell death by necrosis or apoptosis (Radak et al 2017). In this study, Z-GS remarkably improved the neurological outcome and decreased the infarct volume compared with the MCAO group.…”
Section: Discussionmentioning
confidence: 49%
“…These events initiate a complex sequence of signaling cascades that eventually result in neuronal dysfunction and cell death by necrosis or apoptosis (Radak et al . ). In this study, Z‐GS remarkably improved the neurological outcome and decreased the infarct volume compared with the MCAO group.…”
Section: Discussionmentioning
confidence: 97%
“…It should be highlighted that the isolation procedure of unbroken apoptotic bodies from neurological patients blood samples could be of great utility for in vivo study of apoptosis in pathologies, such as cerebral ischemia, multiple sclerosis and Parkinson´s disease, in which alteration of such cell death type has been identified as the main mechanism involved [9][10][11][12]. Specifically, the quantification of circulating isolated apoptotic bodies would potentially serve as a non-invasive tool for determining the degree of apoptotic cell death that has occurred in a particular neurological patient, which is, in fact, highly relevant to the understanding and treatment of such human diseases.…”
Section: Discussionmentioning
confidence: 99%
“…It is now becoming evident that an increasing number of pathological situations can be related to aberrant apoptosis, such as cerebrovascular and neurodegenerative diseases [9][10][11][12]. Thus, the evaluation of the apoptotic processes, in these neurological diseases would be useful in daily clinical practice, since it would allow an earlier and more accurate prognosis, more effective monitoring of evolution of the disease, and the selection of the most appropriate treatment for each patient.…”
Section: Introductionmentioning
confidence: 99%